Strategies For Teaching English Reading Through Islamic Religious Education Content at MA Attarbiyah Addiniyah Al-Amin Gersik - Alfan Hadi; Samsul Hakim (Lembaga Bale Literasi, 2026)
This study aims to describe the English reading learning strategies that are integrated with Islamic Religious Education (PAI) content at Madrasah Aliyah (MA) Attarbiyah Addiniyah Al-Amin Gersik, and to identify the supporting and inhibiting factors involved in their implementation. Madrasah students' low motivation and comprehension when reading English texts are frequently caused by teaching materials that are perceived as insufficiently relevant to their Islamic background. This study employed a qualitative approach with a case study design. Data were collected through classroom observation, in-depth interviews with English teachers and Islamic education teachers, and documentation of the teaching materials used. The data were analyzed by means of data reduction, data display, and conclusion drawing, following the Miles and Huberman model. The findings indicate that the teachers implemented several strategies, namely: (1) the use of reading texts on the themes of prophetic stories, morals (akhlak), and manners (adab) as reading materials; (2) the integration of religious vocabulary with skimming and scanning techniques; (3) the application of content-based instruction that combines religious and linguistic objectives; and (4) collaboration between the English teacher and the Islamic education teacher in developing the materials. These strategies were shown to increase students' motivation, self-confidence, and reading comprehension, since the materials were perceived as being closer to their Islamic experience. This study recommends the more systematic development of Islamic values-based reading materials within the madrasah environment.